2023
DOI: 10.28991/cej-2023-09-01-016
|View full text |Cite
|
Sign up to set email alerts
|

Torsional Behavior of Steel-Concrete-Steel Sandwich Beams with Welded Stirrups as Shear Connectors

Abstract: The structural performance of a steel-concrete-steel sandwich beam (SCSSB) with welded stirrups to the steel skin plates as shear connections exposed to a pure torsion load was studied in this paper. Eight SCSSB specimens were fabricated and tested under pure torsion. The effects of the compressive strength of the concrete core, 26 and 35 MPa, the thickness of the top and bottom steel skin plates, 2 and 4 mm, and the degree of shear interaction, which represents the number of beam stirrups, between the steel s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The criticality of selecting an appropriate mesh size in the finite element method cannot be overstated, as it plays a vital role in the accuracy and reliability of structural simulations; moreover, the partitioning of this mesh necessitates careful consideration to ensure that the chosen size adequately represents the intricacies of the structure [20][21][22][23]. Extensive scholarly discourse in the realm of structural analysis emphasizes the profound impact of mesh size on simulation outcomes [24,25]. Previous research endeavors have demonstrated that variations in mesh size can yield disparate results, thereby underscoring the need for meticulous attention to this parameter.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…The criticality of selecting an appropriate mesh size in the finite element method cannot be overstated, as it plays a vital role in the accuracy and reliability of structural simulations; moreover, the partitioning of this mesh necessitates careful consideration to ensure that the chosen size adequately represents the intricacies of the structure [20][21][22][23]. Extensive scholarly discourse in the realm of structural analysis emphasizes the profound impact of mesh size on simulation outcomes [24,25]. Previous research endeavors have demonstrated that variations in mesh size can yield disparate results, thereby underscoring the need for meticulous attention to this parameter.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…This improvement in the structural integrity becomes more significant than the initial performance. Rehabilitation is the process of reparation and restoration of the performance and strength lost in the structures under varied situations [4][5][6][7]. In the repairing process, the structural members' quality are improved to meet the desired requirements.…”
Section: Introductionmentioning
confidence: 99%